2017
DOI: 10.3389/fcimb.2017.00032
|View full text |Cite
|
Sign up to set email alerts
|

PerC Manipulates Metabolism and Surface Antigens in Enteropathogenic Escherichia coli

Abstract: Enteropathogenic Escherichia coli is an important cause of profuse, watery diarrhea in infants living in developing regions of the world. Typical strains of EPEC (tEPEC) possess a virulence plasmid, while related clinical isolates that lack the pEAF plasmid are termed atypical EPEC (aEPEC). tEPEC and aEPEC tend to cause acute vs. more chronic type infections, respectively. The pEAF plasmid encodes an attachment factor as well as a regulatory operon, perABC. PerC, a poorly understood regulator, was previously s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…PapB and PefB are prototypical members of a family of mobile element-borne fimbrial regulators (61) . They regulate core chromosomal adhesins in Escherichia (62,63). We cloned the pefB homolog under the control of the arabinose promoter to produce pRMPefB.…”
Section: Plasmid-encoded Quinolone Resistance Genes In Fluoroquinolonmentioning
confidence: 99%
“…PapB and PefB are prototypical members of a family of mobile element-borne fimbrial regulators (61) . They regulate core chromosomal adhesins in Escherichia (62,63). We cloned the pefB homolog under the control of the arabinose promoter to produce pRMPefB.…”
Section: Plasmid-encoded Quinolone Resistance Genes In Fluoroquinolonmentioning
confidence: 99%
“…Future research will also be conducted to analyze the functional responses and gene expression profiles of these aEPEC pEAF-carrying strains, including the expression of BFP and the localized adherence phenotype, as well as the regulatory effect of the per locus over the LEE island. In this regard, recent global transcriptional analyses have demonstrated that pEAF genes influence the expression of a number of chromosomal genes in addition to the LEE [ 30 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Along with stimulating virulence gene expression, PerC regulates many genes. RNA-sequencing revealed that PerC regulates, either directly or indirectly, transcription of the fim operon, various metabolism genes, ribosomal RNAs, tRNAs, sRNAs, and others ( Mellies et al, 2017 ). PerC’s mechanism of action has remained largely elusive, but some observations are worth examining.…”
Section: Lee Regulationmentioning
confidence: 99%
“…The intertwined regulation of these important players has implications in interpretation of their observed regulons. For instance, an increase in bfp transcripts in a ler mutant is likely due to decreased repression of perA , a known positive regulator of bfp ( Bustamante et al, 2011 ; Bingle et al, 2014 ; Mellies et al, 2017 ). Conversely, the fim operon was found to be increased in expression in both perC - and ler- deletion mutants.…”
Section: Lee Regulationmentioning
confidence: 99%
See 1 more Smart Citation